Acoustic Absorption of a New Class of Alumina Foams with Various High-Porosity Levels - ZIELIŃSKI, Tomasz G.; POTOCZEK, Marek; ŚLIWA, Romana E.; NOWAK, Łukasz J. (Archives of Acoustics, 2013)
Recently, a new class of ceramic foams with porosity levels up to 90% has been developed as a resultof the association of the gelcasting process and aeration of the ceramic suspension. This paper presentsand discusses original results advertising sound absorbing capabilities of such foams. The authors man-ufactured three types of alumina foams in order to investigate three porosity levels, namely: 72, 88, and90%. The microstructure of foams was examined and typical dimensions and average sizes of cells (pores)and cell-linking windows were found for each porosity case. Then, the acoustic absorption coefficient wasmeasured in a wide frequency range for several samples of various thickness cut out from the foams.The results were discussed and compared with the acoustic absorption of typical polyurethane foamsproving that the alumina foams with high porosity of 88–90% have excellent sound absorbing propertiescompetitive with the quality of sound absorbing PU foams of higher porosity.